Soil-Transmitted Helminth Eggs Are Present in Soil at Multiple Locations within Households in Rural Kenya - Steinbaum, Lauren (PLoS One, 2016)
Almost one-quarter of the world’s population is infected with soil-transmitted helminths (STH). We conducted a study to determine the prevalence and location of STH—Ascaris, Trichuris, and hookworm spp.—egg contamination in soil within rural household plots in Kenya. Field staff collected soil samples from July to September 2014 from the house entrance and the latrine entrance of households in Kakamega County; additional spatial sampling was conducted at a subset of households (N = 22 samples from 3 households). We analyzed soil samples using a modified version of the US Environmental Protection Agency (EPA) method for enumerating Ascaris in biosolids. We found 26.8% of households had one or more species of STH eggs present in the soil in at least one household location (n = 18 out of 67 households), and Ascaris was the most commonly detected STH (19.4%, n = 13 out of 67 households). Prevalence of STH eggs in soil was equally likely at the house entrance (19.4%, N = 67) as at the latrine entrance (11.3%, N = 62) (p = 0.41). We also detected STH eggs at bathing and food preparation areas in the three houses revisited for additional spatial sampling, indicating STH exposure can occur at multiple sites within a household plot, not just near the latrine. The highest concentration of eggs in one house occurred in the child’s play area. Our findings suggest interventions to limit child exposure to household soil could complement other STH control strategies.